PENGARUH CURRENT RATIO DAN NON PERFORMING LOAN TERHADAP RETURN ON EQUITY PADA BANK BUMN - Sahedi; Dicky Zulkarnaen; Gundahara (SUAN PUBLISHER, 2026)
Conventional banks listed on the Indonesia Stock Exchange (IDX) serve as important indicators in assessing national economic stability and performance. Profitability is a key measure of banking performance, commonly assessed using Return on Equity (ROE) to evaluate a bank’s ability to generate profit from shareholders’ equity. This study aims to analyze the effect of the Current Ratio and Non-Performing Loans (NPL) on ROE in State-Owned Banks. The research employs a quantitative approach using secondary data derived from financial statements. Data analysis was conducted using SPSS, including descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that both the Current Ratio and NPL partially have a positive and significant effect on ROE. Simultaneously, both variables also show a positive and significant influence on ROE. The Adjusted R² value of 0.271 suggests that 27.1% of the variation in ROE can be explained by the Current Ratio and NPL, while the remaining 72.9% is influenced by other variables outside the research model